DETERMINANTS OF EXAMINING BEHAVIORAL ASPECTS OF USING EMERGING TECHNOLOGY IN ONLINE FOOD DELIVERY APPS. AN EXTENDED TECHNOLOGY ACCEPTANCE MODEL APPROACH (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose – The study aims to examine factors  that influence customers’ intention to use  emerging technology (such as chatbots,  AI-based recommendations, robotics delivery,  Augmented Reality/Virtual Reality) in  online food delivery applications. The factors  examined in this study are based on the existing  theory of Technology Acceptance Model  (TAM), namely perceived usefulness, perceived  ease of use, attitude towards intention to use the  applications, and this research expanded with  an additional dimension: perceived enjoyment,  which leads to the intention to use online food  delivery services. Design/methodology/approach – The study  employed a quantitative method, and 201  respondents participated in this study. The  questionnaires were distributed using a  convenience sampling technique, and the data  was analyzed using the partial least square  approach. The study focused on measurement  properties via Confirmatory Factor Analysis  (CFA) and SEM using Smart PLS 4.0.  Descriptive analysis and hypothesis testing  provided insights into factors influencing OFD  app adoption among consumers, ensuring  methodological rigor and credibility. Findings – The results show that four (4)  constructs, i.e. Perceived usefulness, Perceived  ease of use, Perceived Enjoyment, and Attitude  towards Behavioral intention. The study  indicates that user experience factors, such  as enjoyment and ease of use, play a crucial  role in determining the behavioral intention  to use technology-based online food delivery  applications in Delhi.
Keywords: Technology Acceptance Model; perceived enjoyment; emerging technologies; online food delivery; and structural equation modeling